321 Occupational exposures to known and suspected carcinogens in the Canadian construction industry. (11th October 2013) - Ge, B; Peters,; Demers,
Abstract : Objectives: CAREX Canada aims to estimate the number of Canadian workers exposed to various carcinogens in the workplace. The objectives of this work is to determine the number of workers exposed to different carcinogens in the construction industry in Canada and identify high risk occupations within the industry for exposure. Methods: Data from the Canadian Workplace Exposure Database (CWED), published relevant Canadian and US scientific literature, data from previous European CAREX projects, government grey literature and other technical reports were used to develop exposure proportions for each occupation in the construction industry. These proportions are combined with 2006 Canadian census of population data to obtain the prevalence of exposure for 30 carcinogens selected to be relevant in the Canadian context. Results: Canadian construction workers, with a total population of 1.07 million, are estimated to have over 1, 188, 000 exposures to the 30 selected carcinogens. Some workers are likely exposed to more than one substance at a time. Carcinogens with substantial number of workers exposed include: solar ultraviolet radiation (343, 000 workers exposed), crystalline silica (240, 000 exposed), wood dust (166, 000 exposed), asbestos (134, 000 exposed), diesel engine exhaust (84, 000 exposed), lead and lead compounds (51, 000 exposed) and bitumen (50, 000 exposed). Jobs at high risk of exposure include construction trade helpers and labourers (290, 000 exposures), carpenters (227, 000 exposures), and heavy equipment operators (127, 000). Quantitative exposure level estimates are available for some carcinogens. Conclusions: Safety in the construction industry has long been the focus of scientific research. Our work shows that workers in this industry are also exposed to a number of known and suspected human carcinogens, with some exposures being very prevalent currently in Canada. Results from our study may be used by occupational exposure and epidemiologic studies to further investigate exposures and occupational cancer in this unique industry.